Budaya Organisasi Sebagai Moderator Pada Pengaruh Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Tenaga Kefarmasian RS Immanuel - Prihartono, Raharjo; Anatan, Lina (SAFE-Network, 2025)
This quantitative study aims to analyze the influence of leadership, work environment, and organizational culture on the performance of pharmaceutical personnel, as well as to examine the role of organizational culture as a moderator in the relationship between leadership and work environment with performance. The research was conducted using a total sampling method involving 89 pharmaceutical personnel at the Pharmacy Installation of Immanuel Hospital Bandung. Data were collected through questionnaires and analyzed using SmartPLS 4.0. The results indicate that organizational culture and work environment have a positive and significant effect on the performance of pharmaceutical personnel, with organizational culture being the dominant factor. Conversely, leadership does not have a positive and significant effect on performance. This aligns with the pre-survey findings, which revealed weaknesses in leadership regarding employee control and complaint handling. Additionally, the performance of pharmaceutical personnel is highly influenced by strict standard operating procedures (SOPs) and regulations, making the role of leadership relatively smaller compared to other factors such as organizational culture and work environment. Organizational culture was not proven to moderate the influence of leadership or work environment on performance. This may be because the organizational culture at Immanuel Hospital is already very strong, so its moderating effect is no longer felt. This is also evident in the role of organizational culture as an independent factor that directly affects performance, rather than as a moderator that strengthens or weakens the influence of leadership and work environment. These findings emphasize the importance of strengthening organizational culture and improving the work environment as the main strategies to enhance the performance of pharmaceutical personnel in the hospital.